Model Perancangan Kawasan Wisata Musik di Kota Ambon Dengan Pendekatan Arsitektur Simbiosis - Matias Sabono; Noviar Nurdin Kasim; Faizah Mastutie (Universitas Muslim Indonesia, 2022)
Ambon City is the center of the port, tourism, and education in the Maluku archipelago. Ambon City and music cannot be separated, even music has become the core movement of the city known as Ambon Manise because musical intuition is naturally inherent in Ambonese life. The development of music in the city of Ambon is very fast, Ambon is a city that has a lot of music enthusiasts, and has even become one of the cities that produce famous music artists in Indonesia. In the mid-20th century, Ambon produced famous singers from national to international levels. This makes Ambon city chosen by UNESCO as one of the world's creative music cities. In developing Ambon City as a world music city, the Ambon City government has prepared 25 plans which are divided into five pillars, namely musicians and communities, infrastructure, education, industrial development, and socio-cultural values. The five pillars are development priorities and development towards one icon, namely Ambon City of Music